Adding to the midwifery curriculum through internationalisation and promotion of global mobility - Williams, Jacqui; Hulme, Gemma; Borrelli, Sara E. (Mark Allen Healthcare, 2017)
Despite the obvious need for student midwives to be exposed to meaningful learning experiences that consider engagement in the wider context of international health care and the associated benefits, there is a lack of information on how this is achieved within midwifery curricula both nationally and internationally. At the University of Nottingham, work has been undertaken to ensure the midwifery curriculum is internationalised and global mobility is promoted to all midwifery students. Processes and strategies have been put in place to encourage students' mobility including the Erasmus+ programme, elective placements and short-term ad hoc international opportunities. Thanks to the strategies that have been implemented, the Division of Midwifery has seen an increase in students undertaking an international placement from 5% in 2013/14 to 18% in 2015/16. Moving forward, future works will aim to develop ‘virtual mobility’ projects and evaluate the Erasmus+ programme in conjunction with European partners.